IMPLEMENTASI MODEL DISCOVERY LEARNING DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS DAN HASIL BELAJAR SISWA MATA PELAJARAN BAHASA ARAB DI MTS RAUDLATUL MUBTADIIN KALIWADAS - Agis Selviani; Septi Gumiandari (CV. ADIBA ASIHA AMIRA, 2023)
At first, Arabic language lessons at MTs Raudatul Mubtadi’in were still very low regarding students’ critical thinking, and there were students learning difficulties in understanding Arabic, so there was a need to find a way to overcome this problem, namely by applying the discovery learning method with a scientific approach so that students could improve. Students’ critical thinking. The aim of this research is to improve critical thinking skills, develop a Discovery learning model with a scientific approach and student learning outcomes in the Arabic language subject at MTS Raudhatul Mubtadi’in Kaliwadas. This research uses qualitative methods with a scientific approach. The subjects of this research were 25 students of class IX MTS Raudatul Mubtadi’in. Data sources come from teachers, students and documents. Based on the research results, the learning process by applying the discovery learning model using a scientific approach can improve critical thinking skills and student learning outcomes. The conclusion of this research is that the application of the discovery learning model using a scientific approach can improve critical thinking skills and maximum and effective learning outcomes in MTS Raudlatul Mubtadiin Kaliwadas Arabic language lessons.